We will not cancel us ebook And other dreams of transformative justice. - brown, adrienne maree (Emergent Strategy., 2020)
Cancel culture addresses real harm...and sometimes causes more. It's time to think this through. "Cancel" or "call-out" culture is a source of much tension and debate in American society. The infamous "Harper's Letter," signed by public intellectuals of both the left and right, sought to settle the matter and only caused greater division. Originating as a way for marginalized and disempowered people to take down more powerful abusers, often with the help of social media, cancel culture is seen by some as having gone "too far." Adrienne maree brown, a respected cultural voice and a professional mediator, reframes the discussion for us, in a way that points to possible ways beyond the impasse. Most critiques of cancel culture come from outside the milieus that produce it, sometimes from even from its targets. Brown explores the question from a Black, queer, and feminist viewpoint that gently asks, how well does this practice serve us? Does it prefigure the sort of world we want to live in? And, if it doesn't, how do we seek accountability and redress for harm in a way that reflects our values?